2004
DOI: 10.1021/ac0351670
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Effects of Weak Acids on Negative-Ion Electrospray Ionization Mass Spectrometry

Abstract: Despite widespread use in pharmacokinetic, drug metabolism, and pesticide residue studies, little is known about the factors governing response during reversed-phase liquid chromatography coupled with negative-ion electrospray ionization (ESI(-)) mass spectrometry. We examined the effects of various mobile-phase modifiers on the ESI(-) response of four selective androgen receptor modulators using a postcolumn infusion system. Acetic, propionic, and butyric acid improved the ESI(-) responses of analytes to vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
149
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(166 citation statements)
references
References 45 publications
16
149
1
Order By: Relevance
“…For our studies, acetic acid was employed for acidification to circumvent the problem of signal suppression. Other investigators have previously observed changes in electrospray response upon acidifying the analyte solution with acetic acid [17,18]. The studies presented here are, however, unique in that the observed responses in acidified and neat methanol are compared with the calculated concentration of the protonated form of the analyte in each solution.…”
Section: Influence Of Solution Ph On Electrospray Responsementioning
confidence: 89%
“…For our studies, acetic acid was employed for acidification to circumvent the problem of signal suppression. Other investigators have previously observed changes in electrospray response upon acidifying the analyte solution with acetic acid [17,18]. The studies presented here are, however, unique in that the observed responses in acidified and neat methanol are compared with the calculated concentration of the protonated form of the analyte in each solution.…”
Section: Influence Of Solution Ph On Electrospray Responsementioning
confidence: 89%
“…It was assumed that utility of 75% of the organic modifiers in these solutions were sufficient to represent their effect to these chiral molecular recognition systems. Formaldehyde incorporation (100 mM) to enhance spectral quality of previously reported experiments was not practiced in these experiments, 28,32 because the study was focused on studying the effects by electrospray friendly organic solvent modifiers on these chiral recognition systems. It was assumed that formaldehyde incorporation with a high concentration (100 mM) would influence the solvent properties and alter the original form of the solvent system.…”
Section: Experimental Section Materialsmentioning
confidence: 99%
“…3 Gas chromatography combined with mass spectrometry (GC/MS) and liquid chromatography combined with mass spectrometry (LC/MS) have been utilized for the analysis of insecticides and pesticides in water. [4][5][6][7][8][9][10] Due to the high solubility of xylenols and their isomers of ethylphenols, LC/MS was tried, but was unsuccessful in separating these chemical species. Analyses of these compounds using GC/MS have been reported elsewhere.…”
Section: Introductionmentioning
confidence: 99%